Arsy - Versy - Remo, Miro (VŠMU, 2009)
Verzio FF Submission "Arsy-Versy" is the story of a mother and her son Lubos. Deciding to escape the world of people, so full of hypocrisy and banality, Lubos chooses to live in harmony with nature, choosing to fly away into a world where only bats, intelligent creatures as he sees them, live.